A Molecular Photosensitizer in a Porous Block Copolymer Matrix‐Implications for the Design of Photocatalytically Active Membranes. Issue 68 (12th October 2021) - Chettri, Avinash; Kruse, Jan‐Hendrik; Kumar Jha, Keshav; Dröge, Lara; Romanenko, Iuliia; Neumann, Christof; Kupfer, Stephan; Turchanin, Andrey; Rau, Sven; Schacher, Felix H.; Dietzek, Benjamin
Abstract: Recently, porous photocatalytically active block copolymer membranes were introduced, based on heterogenized molecular catalysts. Here, we report the integration of the photosensitizer, i. e., the light absorbing unit in an intermolecular photocatalytic system into block copolymer membranes in a covalent manner. We study the resulting structure and evaluate the orientational mobility of the photosensitizer as integral part of the photocatalytic system in such membranes. To this end we utilize transient absorption anisotropy, highlighting the temporal reorientation of the transition dipole moment probed in a femtosecond pump‐probe experiment. Our findings indicate that the photosensitizer is rigidly bound to the polymer membrane and shows a large heterogeneity of absolute anisotropy values as a function of location probed within the matrix. This reflects the sample inhomogeneity arising from different protonation states of the photosensitizer and different intermolecular interactions of the photosensitizers within the block copolymer membrane scaffold. Abstract : A Ru photosensitizer covalently bound to a porous block copolymer membrane to be used in photocatalytic systems exhibits an additional charge transfer process unobserved in aprotic solvents due to protonation from water molecules absorbed in the polymer. The inhomogeneity due to different orientations of the bound photosensitizer together with its rigidity in the polymer could serve as important set screws for controlling the overall photocatalytic efficiency.